ARTIFICIAL INTELLIGENCE (AI) ASSISTED MULTIMODALITY IN DIGITAL CAMPAIGN TEXTS IN THE PRESIDENTIAL ELECTION - Putri, Dian Marisha; Mulyadi, Mulyadi; Rangkuti, Rahmadsyah; Saragih, Amrin; Amri, Yusni Khairul (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
This study examines the multimodality of verbal and visual modes in 2024 digital campaign texts combining linguistic approaches with artificial intelligence technology. Verbal mode analysis involves the use of multiple modes in discourse (Kress & Van Leeuwen, 2001). The use of AI helps identify patterns of visual-verbal relationships. The data and data sources are campaign texts for the 2024 General Election. Five social media platforms were used: WhatsApp, Facebook, Twitter, TikTok, and Instagram. Five online media platforms were selected: a) Detik.com, b) Kompas.com, c) Tribunnews.com, d) Liputan6.com, and e) cnbcindonesia.com. A total of 200 election texts were collected between May 2023 and February 2024. The collected data were qualitatively reviewed in the form of digital texts. The analysis results illustrate that AI-assisted multimodality in explaining the meaning of text in visual and verbal modes, such as: a) strengthening the meaning of the text. b) using a sarcastic style of language. c) The role of meaningful visual text has a relational nature: between illustrations and silhouettes, followed by the attributes of text as a material process. d) representing campaign text refers to how the semiotic system on objects and relationships outside the text and context, both directly and indirectly. The findings demonstrate that the visual language representing political campaign text serves as both an action and a reaction process, as well as a verbal and mental process, within the context of the situation.